The Effect of Financial Capital, Labor and Social Capital on The Income of Culinary Smes in Jagakarsa District - Rukijati Widjianingsih, Rukijati Widjianingsih; Bachtar Bakri, Bachtar Bakri; Ign.A.Wirawan Nugrohadi, Ign.A.Wirawan Nugrohadi; Tri Suratmi, Tri Suratmi (LPPM Universitas Respati Indonesia, 2023)
MSMEs need encouragement from all parties in Indonesia to develop into an economic power in society. One type of UMKM is the culinary industry which represents Indonesian culture regarding variations in taste and people's tastes for authentic food from various regions. During the Covid-19 pandemic, culinary MSMEs in Jagakarsa District, South Jakarta, experienced a decrease in income. This research was conducted with the aim of analyzing the effect of financial capital, labor, and social capital on the income of culinary MSMEs in Jagakarsa District.This research is an analytical survey with a quantitative approach, using a sample of 84 SMEs taken from the population using an accidental technique. The research instrument uses a questionnaire constructed by researchers based on variable indicators. Data analysis using multiple linear regression was carried out with software applications on computer devices. The results showed that financial capital, labor, and social capital had an independent effect on the income of MSME actors, with figures of 0.394, 0.792, and 0.234. Financial capital, labor, and social capital have also proven to have a joint effect in increasing the income of culinary MSMEs in Jagakarsa.The conclusion that can be conveyed is that MSMEs need stimulus from various parties, especially from the government and stakeholders to develop. Stimulus can be in the form of policies, capital, and training for human resources to behave hygienically because the food industry is related to health problems. Keywords: taste, taste, presentation, typical Indonesian food